THE EFFECT OF LIQUIDITY AND PROFITABILITY ON STOCK PRICES IN AUTOMOTIVE SUB-SECTOR MANUFACTURING COMPANIES AND COMPONENTS LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2019 - 2021 - Tita Kartika; Siti Nur Fadrin (LPPM Universitas Sebelas April, 2023)
This study aims to examine and analyze the effect of liquidity and profitability onstock prices in automotive and component sub-sector manufacturing companies on theIndonesia Stock Exchange in 2019-2021. By using purposive sampling method, this researchsample consists of 4 companies. The analytical method used in this study is multiple linearregression analysis, correlation coefficient analysis, analysis of the coefficient ofdetermination, and hypothesis testing (t test and f test). The results of the liquidity t testusing the current ratio indicate that there is a negative and significant effect on stock prices.Meanwhile, profitability using return on assets indicates that there is no significant effect onstock prices. The results of the f test show that together the variables of liquidity using thecurrent ratio and profitability using return on assets have a positive and significant effect onstock prices. Based on the results of the determination test, liquidity using the current ratioand profitability using return on assets has an effect of 49.4% on stock prices, the other50.6% is influenced by other factors that are not included in the research variables.